2018
DOI: 10.1098/rspb.2018.0722
|View full text |Cite
|
Sign up to set email alerts
|

The lingering impact of stress: brief acute glucocorticoid exposure has sustained, dose-dependent effects on reproduction

Abstract: Acutely stressful experiences can have profound and persistent effects on phenotype. Across taxa, individuals differ remarkably in their susceptibility to stress. However, the mechanistic causes of enduring stress effects, and of individual differences in stress susceptibility, are poorly understood. Here, we tested whether brief, acute increases in glucocorticoid hormones have persistent effects on phenotype, and whether effects differ according to the magnitude or duration of elevation. We used a novel metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
54
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 54 publications
(74 citation statements)
references
References 54 publications
3
54
1
Order By: Relevance
“…Though we did not measure fitness in this study, the differences we found in adult CORT responses to challenges based on developmental environment could have fitness consequences. The previous work in this study population showed that females that received exogenous CORT designed to simulate higher or longer acute stress responses during incubation later provisioned at lower rates, resulting in smaller and lighter offspring (Vitousek, Taff, Ardia, et al, ). As demonstrated in this study, nestling tree swallows with lower mass can have a smaller chance of survival.…”
Section: Discussionmentioning
confidence: 80%
See 3 more Smart Citations
“…Though we did not measure fitness in this study, the differences we found in adult CORT responses to challenges based on developmental environment could have fitness consequences. The previous work in this study population showed that females that received exogenous CORT designed to simulate higher or longer acute stress responses during incubation later provisioned at lower rates, resulting in smaller and lighter offspring (Vitousek, Taff, Ardia, et al, ). As demonstrated in this study, nestling tree swallows with lower mass can have a smaller chance of survival.…”
Section: Discussionmentioning
confidence: 80%
“…The consequences of this relationship for adult fitness are likely highly context‐specific because the relationships between CORT phenotype and fitness are complex and context‐dependent (Vitousek, Taff, Hallinger, et al, ). In this breeding population of tree swallows, there is some evidence that females with low stress responses and low baseline CORT during incubation have greater reproductive success (Vitousek, Taff, Ardia, et al, ; Vitousek, Taff, Hallinger, et al, ). Therefore, our results suggest that individuals that experienced warmer temperatures during the incubation stage of development could, in certain contexts, have increased reproductive success.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Predation rates are very low at our sites, but we were careful not to include any nests that failed due to predation or other known causes. One of the females categorized as “stress‐susceptible” received corticosterone doses after sample collection as part of a separate experiment, but these treatments do not increase abandonment rate in our population (Vitousek, Taff, Ardia, et al, ). Females that abandoned after receiving a handicapping treatment and females that successfully breed under benign conditions could not be placed into a resilience category and were not included in MeDIP analyses for this predictor (Figure ).…”
Section: Methodsmentioning
confidence: 98%